Creditor-Psychology, with Special Emphasis on the Eurozone Crisis. (13th May 2015) - Caya, Sinan
Abstract: Creditors seem to share a common psychological profile, which, moreover, applies to legal personalities, besides individuals. It could be possible to shed some light onto the recent (and for many scholars ongoing) economical crisis of the European Union (which also triggers social and political repurcussions), by an analysis of the creditors' traditionally encountered attitudes and moods towards their debtors, which are handled in this article. The prominant "ingredient" involves a keen fear regarding the re-gain of the lent amount, let alone the interests.